Cardiac and Carotid Markers Link With Accelerated Brain Atrophy: The AGES–Reykjavik Study (Age, Gene/Environment Susceptibility–Reykjavik). Issue 11 (November 2016) - Sabayan, Behnam; van Buchem, Mark A.; Sigurdsson, Sigurdur; Zhang, Qian; Meirelles, Osorio; Harris, Tamara B.; Gudnason, Vilmundur; Arai, Andrew E.; Launer, Lenore J.
Abstract : Objective—: Pathologies in the heart–brain axis might, independently or in combination, accelerate the process of brain parenchymal loss. We aimed to investigate the association of serum N-terminal brain natriuretic peptide (NT-proBNP), as a marker of cardiac dysfunction, and carotid intima media thickness (CIMT), as a marker of carotid atherosclerosis burden, with structural brain changes. Approach and Results—: In the longitudinal population-based AGES–Reykjavik study (Age, Gene/Environment Susceptibility–Reykjavik), we included 2430 subjects (mean age, 74.6 years; 41.4% men) with baseline data on NT-proBNP and CITM (assessed by ultrasound imaging). Participants underwent a high-resolution brain magnetic resonance imaging at baseline and 5 years later to assess total brain (TBV), gray matter, and white matter volumes. Each unit higher log-transformed NT-proBNP was associated with 3.6 mL (95% confidence interval [CI], −6.0 to −1.1) decline in TBV and 3.5 mL (95% CI, −5.7 to −1.3) decline in gray matter volume. Likewise, each millimeter higher CIMT was associated with 10.8 mL (95% CI, −17.3 to −4.2) decline in TBV and 8.6 mL (95% CI, −14.4 to −2.8) decline in gray matter volume. There was no association between NT-proBNP and CIMT and changes in white matter volume. Compared with participants with low NT-proBNP and CIMT, participants with both high NT-proBNP and CIMT had 3.8 mL (95% CI, −6.0 to −1.6) greater decline in their TBV and 4 mL (95% CI, −6.0 to −2.0) greater decline in GMW. These associations were independent of sociodemographic and cardiovascular factors. Conclusions—: Older subjects with both cardiac dysfunction and carotid atherosclerosis are at an increased risk for brain parenchymal loss. Accumulated pathologies in the heart–brain axis might accelerate brain atrophy. Abstract : Supplemental Digital Content is available in the text.